2017
DOI: 10.5334/egems.214
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Data Quality Assessment Results: Identifying Individual and Organizational Barriers and Solutions

Abstract: Introduction:Electronic health record (EHR) data are known to have significant data quality issues, yet the practice and frequency of assessing EHR data is unknown. We sought to understand current practices and attitudes towards reporting data quality assessment (DQA) results by data professionals.Methods:The project was conducted in four Phases: (1) examined current DQA practices among informatics/CER stakeholders via engagement meeting (07/2014); (2) characterized organizations conducting DQA by interviewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…As there were no guidelines specifically designed to guarantee high‐resolution data quality, 9,14 we elaborated the first complete validation procedure. Our validation procedure was inspired by previously published experiences 9,10,30,32‐34 and guidelines 13‐15,28,35 regarding data quality assessment in the field of medical DB collected at a lower rate or in a restricted area. To evaluate the quality of the data, we chose to perform an external validation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there were no guidelines specifically designed to guarantee high‐resolution data quality, 9,14 we elaborated the first complete validation procedure. Our validation procedure was inspired by previously published experiences 9,10,30,32‐34 and guidelines 13‐15,28,35 regarding data quality assessment in the field of medical DB collected at a lower rate or in a restricted area. To evaluate the quality of the data, we chose to perform an external validation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, a validation step of the collected data is necessary before considering this DB suitable for research purposes 9‐11 . Indeed, the value of research findings depends on data quality 12,13 . Several guidelines or frameworks were elaborated to evaluate and report the quality of DBs and national registries and to guide designers of DBs at each step of the data collection 12,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of data quality is key for ensuring that the available data and information are credible and such assessments are essential when establishing trust for reuse of the data (Callahan 2017). Trusted data are perceived as worthy of use in decision making environments where the metadata is sufficient to adequately describe the data, e.g., information about the dataset author and data timeliness.…”
Section: Needs For Curating and Sharing Dataset Quality Informationmentioning
confidence: 99%
“…Investigating barriers to assessing and reporting data quality information in medical bioinformatics, Callahan et al (2017) identified issues, at both organizational and individual levels, that contribute to deficiencies in quality assurance. Such organizational issues include inadequate support, unclear expectations and insufficient training such as the absence of best practices.…”
Section: Needs For Curating and Sharing Dataset Quality Informationmentioning
confidence: 99%
“…In any case, the common key is the idea of a DQ assessment is imperative to assure the data fitness-to-use. In this sense, DQ assessment methods emerge as an artifact helping in the community acceptance of the results of research works [7], and standardizing these methods could lead the transparency and consistency of DQ concept [8].…”
Section: Motivationmentioning
confidence: 99%